An in-depth PRISMA based review of cybercrime in a developing economy: Examining sector-wide impacts, legal frameworks, and emerging trends in the digital era - Noor Uddin Milon, Md; Ghose, Provakar; Chowdhury Pinky, Tania; Nowshin Tabassum, Mst.; Nazmul Hasan, Md; Khatun, Maimuna (Edelweiss Applied Science and Technology, 2024)
In today’s digital age, the swift advancement of information and communication technology (ICT) has brought immense benefits to humanity, but it has also opened the door to various technological crimes, particularly cybercrime, which is becoming an increasingly significant issue in Bangladesh. This paper aspires to critically examine the nature and scope of cybercrime in Bangladesh, exploring its impact on individuals, businesses, and the economy as a whole. This study investigates the state of cybercrime in Bangladesh, its sector-wide impacts, and the effectiveness of existing legal government law in combating these crimes. a survey alongside semi-structured interviews and a variety of sources, including Scopus, Web of Science, DOAJ, Scimago, and Google Scholar databases. The study also utilized PRISMA based methodology to find out the research gaps in the context to increase deeper insights and understanding into technology-related crimes. Cybercrime (hacking, phishing and credit Card Fraud, financial fraud etc) greatly affected economic growth, emerging trends, different sectors, banking, finance and legal frameworks which are emerging economies that have the mediation process of expanding factors in Bangladesh. Additionally, financially motivated attackers, politically motivated attackers and espionage motivated attackers are the main reasons for cybercrime. As Bangladesh rapidly adopts digital technologies, the study identifies the emerging factors, patterns, underlying logic, the role of law enforcement agencies and cybersecurity measures related to cybercrime. The implication will be presented in the increasingly alarming consequences of cybercrime and suggests strengthening existing global cyber laws to more effectively fight these crimes.